PENGARUH KONDISI DAN KOSENTRASI BELAJAR DI RUMAH PADA MASA PANDEMI COVID-19 TERHADAP PRESTASI BELAJAR SISWA KELAS X MAN PEMATANGSIANTAR - Saragih, Marlindoaman; Nurjana, Pelita (Jurnal Metabio, 2021)
This study aims to determine the effect of conditions and concentration on learning at home during the COVID-19 pandemic on the academic achievement of grade X students at MAN Pematangsiantar in the 2020/2021 academic year. The population in this study was grade X, consisting of four classes with 160 students. A sample size of 25% of the total population was taken, resulting in a sample size of 160 x 25% = 40 students. The research instruments used to collect data were student questionnaires and the Student Grade List (DKN). The remainder was collected through documentation as supplementary data. The results of this study indicate that the conditions and concentration on learning during the COVID-19 pandemic significantly impacted the academic achievement of grade X students at MAN Pematangsiantar.